Tlingit canoes in Yakutat Bay, Yakutat Alaska, 1899 - Harriman, Edward Henry, 1848-1909 Devereux, W. B.
Two photos on mount. Photo on right (no.24) by W.B. Devereux, Yakutat men and boy in two canoes pulled up beside a large expedition boat. Photo on left (no. 67) by Edward D. Harriman, two men paddle a pair of canoes across water with ice floes. Caption on mount: Yakutats.